THE EFFECT OF FLUENCY IN RECITING AL-QUR'AN ON MASTERY OF ARABIC READING SKILLS IN CLASS VII STUDENTS OF MTSN 4 HULU SUNGAI UTARA SOUTH KALIMANTAN - Hasanah, Norida Tiara; Noor, Fatwiah (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
In learning Arabic, there are four skills that must be mastered by students. One of them is reading skill. This thesis presents the Influence of Fluency in Reciting al-Qur'an on the Mastery of Reading Skills for class VII students of MTsN 4 HSU. The background of this research is that there are still some students who are still not fluent in reading skills, while the Al-Qur'an recitation program has been implemented at the school. Therefore, the researcher wants to examine this research to find out whether there is influence and how much influence the program has to improve the mastery of reading skills of class VII students. This type of research is field research, using a statistical quantitative approach. The population of this study were all students of class VII, a total of 38 people, using a saturated sample. By collecting data in the form of tests, interviews, observations and documentation. As for processing techniques and data analysis using descriptive statistical analysis and inferential statistics using simple linear regression. The results of this study indicate that the average score of the Al-Qur'an memorization test is included in the very good category with a score of (80.21). Likewise, the average score of the reading skill test is included in the very good category with a score of (84.39). And based on the results of calculations using the simple linear regression formula, it can be seen that there is a significant influence between the ability to fluency in Reciting al-Qur'an in the Mastery of Skills for class VII students with a value of 72%.